2011
DOI: 10.1002/pi.3137
|View full text |Cite
|
Sign up to set email alerts
|

Block copolymers as polymeric stabilizers in non‐aqueous emulsion polymerization

Abstract: This review summarizes the background and recent advances of block copolymer stabilized oil‐in‐oil emulsions. For non‐polymerizable emulsions which have promising application possibilities for biomedical and cosmetic formulations, it is shown that tailor‐made block copolymers are by far the most efficient stabilizers with respect to low molecular weight surfactants. The characteristic features of oil‐in‐oil emulsions comprising one polymerizable phase are described. These types of non‐aqueous emulsions are of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 87 publications
(140 reference statements)
0
41
0
Order By: Relevance
“…In the present study, hexaphenylbenzene (HPB) was chosen as the large hydrophobic section and PEG as hydrophilic part of the amphiphile on the account of their large antagonistic forces . Smaller amphiphiles like sodium dodecyl sulfate or lutensols with high critical micelle concentration (cmc) form only small aggregates (micelles) while amphiphilic block copolymers yield kinetically arrested non‐equilibrium structures . Additionally, we favored the propeller‐like HPB over the corresponding dehydrogenated disk‐like hexa‐ peri ‐hexabenzocoronene (HBC) as hydrophobic building block.…”
mentioning
confidence: 99%
“…In the present study, hexaphenylbenzene (HPB) was chosen as the large hydrophobic section and PEG as hydrophilic part of the amphiphile on the account of their large antagonistic forces . Smaller amphiphiles like sodium dodecyl sulfate or lutensols with high critical micelle concentration (cmc) form only small aggregates (micelles) while amphiphilic block copolymers yield kinetically arrested non‐equilibrium structures . Additionally, we favored the propeller‐like HPB over the corresponding dehydrogenated disk‐like hexa‐ peri ‐hexabenzocoronene (HBC) as hydrophobic building block.…”
mentioning
confidence: 99%
“…BMIm[PF 6 ]-in-oil 6 ]-inwater system, polymeric surfactants are efficient in the stabilization of the ionic liquid droplets [65]; therefore, the surfactant Bu-PVP was changed to poly(1-ethenylpyrrolidin-2-one/hexadec-1-ene (Agrimer AL22). Agrimer AL22 is a block co-polymeric surfactant with a HLB lower than 15 (HLB = 3-5) and therefore should enable the stabilization of the BMIm[PF 6 ] droplets within the oil phase.…”
Section: Preparation Of Bmim[pf 6 ] Polyurea Microcapsules Via Bmim[pmentioning
confidence: 99%
“…Non‐aqueous or anhydrous emulsions with their application possibilities have been described in several recent review articles . An almost exclusively steric stabilization was provided for these emulsions and different authors have demonstrated that polymeric surfactants, such as block or graft copolymers, are more efficient stabilizers than low molecular weight surfactants …”
Section: Introductionmentioning
confidence: 99%